Multilayered Bio-Based Electrospun Membranes: A Potential Porous Media for Filtration Applications - Neisiany, Rasoul Esmaeely; Enayati, Mohammad Saeid; Kazemi-Beydokhti, Amin; Das, Oisik; Ramakrishna, Seeram (Frontiers in Materials, 2020)
Amongst the different polymeric membranes, electrospun membranes have shown promising performance for filtration applications through the facile and controlled preparation method leading to tailored material structure. Furthermore, multilayered bio-based electrospun membranes exhibited superior filtration performance, considering they are eco-friendly with superior mechanical properties and better adsorption efficiency compared to the single-layered electrospun membranes. The aim of this mini-review is to reveal the current state-of-art of the development of multilayered bio-based electrospun membranes and to provide new insights into the future of tailored membranes towards practical applications.